KAJIAN HUBUNGAN RESIPROKAL ANTARA PENERIMAAN DAN PENGELUARAN PEMERINTAH (Studi Kasus di Indonesia Periode 1969-2011) - Dedi Supriadi; Munawar Ismail (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study examined the reciprocal relationship between the Indonesian government revenues and expenditures using annual data in the period 1969-2011. This study also examined the influence of control variables for economic growth, inflation, international oil prices, and oil and monetary crisis on government revenues and expenditures. By using the Two-Stage Least Square Analysis, this research has obtained the conclusion that the relationship between revenues and expenditures have relationship patterns that support the fiscal synchronization hypothesis. While economic growth, inflation and international oil prices and the economic crisis dummy variables as control variables have varied influences.Keywords: Government Revenue, Government Expenditure, Fiscal Synchronization,TSLS